Hubungan Tingkat Depresi Dengan Kejadian Insomnia - Marwa, Mentari (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
This study aimed to know the correlation between depression and occurrence of insomnia in elderly. The level of depression as independent variables and the incidence of insomnia as the dependent variable, the elderly in nursing research subjects Wredha Santo Yoseph Kediri with an age range 65-90 years, amounting to 22 elderly. Saturated sampling is used as a method of making the subject. Data analysis using Spearman correlation analysis and data collection using a scale of Geriatric Depression Scale (GDS) and Insomnia Rating Scale (IRS). The results showed that 11 elderly (50.0%) with moderate depression, 6 elderly people (27.3%) with severe depression, and 5 elderly (22.7%) with mild depression. The level of insomnia in elderly as much as 15 elderly (68.2%) with moderate of insomnia, 4 (18.2%) with mild of insomnia, and 3 (13.6%) with severe of insomnia. Depression is related to occurrence Insomnia with coefficient r 0.692, p = 0.000. These results suggest that increasing levels of depression will improve insomnia in elderly, and vice versa